Volume 1: Offshore Technology 2018
DOI: 10.1115/omae2018-77095
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Bolt Tightening Sequences in Bolted Joints Using Superelement FE Modeling Technique

Abstract: A lot of effort is put to achieve bolt preload uniformity during the assembly process of offshore bolted joint connections resulting in potentially high economic costs and project delays. The complexity of this operation is due to the effect of the elastic interaction between the different joint elements which causes load variations of adjacent bolts whenever a bolt is tightened. As a consequence, it is difficult to achieve a uniform target load in the bolts. In order to avoid this phenomenon, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is suggested that more than one pass be made on each bolt in the same sequence to ensure that any deformation in the flange or relaxation of bolts is accounted for [20,21]. To simulate this, a second pass was made using sequence A.…”
Section: Tightening Sequence and Number Of Passesmentioning
confidence: 99%
“…It is suggested that more than one pass be made on each bolt in the same sequence to ensure that any deformation in the flange or relaxation of bolts is accounted for [20,21]. To simulate this, a second pass was made using sequence A.…”
Section: Tightening Sequence and Number Of Passesmentioning
confidence: 99%